ANALISIS CAKUPAN LAYANAN WI-FI GEDUNG PASCASARJANA UNIVERSITAS UDAYANA - Dhiko Pradnyana, Putu; Wiharta, D.M.; Sastra, N.P. (Jurnal SPEKTRUM; Vol 6 No 2 (2019): Jurnal SPEKTRUM, 2019)
The main changes in the telecommunication during these present days come mainly from wired technology to wireless technology. The Wireless LAN (WLAN) configuration consists of an access point, connected to users using air medium. The postgraduate building of Universitas Udayana has been equipped with a wireless network, supporting the study activities within the building. This research explains regarding the signal level quality and the Quality of Service (QoS) by analyzing the Wi-Fi coverage. The measurements were divided into two models, with and without barriers. The highest result comes to -42 dBm, conversely, the lowest is -82 dBm. Thus, the results show that the throughput value is 3.97 Mbps. Within the maximum bandwidth of 10 Mbps, the average packet-loss is not more than 3%. The delay measurement provides a result of not more than 100 ms, and the jitter obtained is 0.04. According to the digital floor plan, the calculation results of the coverage area match the signal level measurement.